Analyzing the relations between menu features and customer intention to use for self service kiosk at McDonald - Shaharin, Norshahira; Musa, Haslinda; Abdul Rashid, Nurulizwa; Masellin, Carol Angela; Al-Shami, Samer Ali Hussein; Jopri, Mohd Hatta (Human Resource Management Academic Research Society, 2024)
Self-service technologies have been defined as a technical interface that allows clients to create services without the assistance of a service representative. As the food service sector grows, technology advances that improve service operations are being developed and deployed at a rapid pace. In general, self-service kiosks are designed to provide prompt service, eliminate the ordering line, and increase sales revenue. However, the majority of selfservice kiosk research focuses on technology adoption behavior, with limited research on menu features. Therefore, this study aims to analyze customer intention to use self-service kiosk (SSK) services based on menu feature factors. This research builds on previous studies showing customer satisfaction with SSK services at McDonald’s. The kiosks are part of McDonald’s modernization program, Nxtgen, offering a digitized alternative for ordering and paying, ensuring a more seamless transaction process. The study investigates the indirect effects of menu visual appeal, menu informativeness, design, and perceived control on customers' preferences for using kiosks instead of going to the counter at McDonald’s. A quantitative method was chosen for data collection, utilizing the Statistical Package for the Social Sciences (SPSS) version 22 for data analysis. The study's questionnaire will be distributed to 150 respondents in Malaysia who have used McDonald’s kiosks, through various platforms such as WhatsApp, Telegram, Facebook, and other network-based applications. The analysis of the collected data reveals that four independent variables have a significant relationship with the dependent variable, providing beneficial insights for McDonald’s to adapt and retain their competitive edge despite the challenges posed by the crisis.